Geometry Introduction Learning Assessment Through Smart Books at Almawaddah IT Kindergarten - Pramita, Miki Ayu; Alfauzan Amin; Desi Tri Anggereni (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to develop and implement appropriate geometric educational teaching aids for early childhood (PAUD), and to measure their influence on the understanding of the concept of plane figures (triangle, square, rectangle, circle, quadrilateral, pentagon, hexagon). The study uses an R&D (Research & Development) approach with the following stages: (1) designing props made of felt, (2) limited trials in PAUD classes, (3) evaluation through comprehension and observation tests. The results show that the use of props significantly increases students' understanding scores compared to before use, as well as increasing motivation and learning activities. These findings indicate that well-designed, interactive and kinesthetic geometric teaching aids can be an effective medium in geometry learning for PAUD. Practical implications for PAUD teachers and learning media developers are outlined.